Ohmic heater for extracting essential oils from aromatic plants - Valderrama Gutierrez, Freddy Fernando (Scientia et Technica, 2018)
Ohmic heating technology (OH) promises to be an efficient alternative compared to the classic processes of heat transfer. OH is characterized by rapid and uniform heating, which makes it an appropriate technology for the food industry. This paper shows the design and construction of an ohmic heating chamber for methodological purposes, and used for the extraction of essential oils from aromatic plants; the design restrictions are mainly electrical and geometric. The main design constraints are extraction power and volumetric capacity. Two geometries are proposed and analyzed in order to design the heating chamber, only the axial electric field geometry achieves the requirements. Finally, the results of an essential oil extraction experiment are reported, in order to verify the performance of the built chamber.